Literature, capitalism and revolution - Martínez Matías, Paloma (ARFIL y UNL, 2022)
This paper analyzes the relationship that Walter Benjamin establishes between literary criticism and politics through the study of the two most relevant essays that he devotes to literary creation in France and in which he gives a prominent position to surrealism. In both essays Benjamin examines the role that intellectuals play in capitalist society by adopting a political position that openly advocates the revolutionary path to solve the structural problems generated by capitalism. Thus, his reflections on the twentieth –century French novel, as well as his interpretation of André Breton’s novel Nadja, will be used as a basis for providing an interim answer to questions concerning Benjamin’s view of the alleged autonomy of art, the theoretical referents that determine his understanding of revolution and how he conceives the work of literary criticism in this context.